ANALISIS KONSTRUKSI NILAI-NILAI BUDAYA DAN KARAKTER ISLAMI DALAM CERITA PENDEK PADA BUKU AJAR DI MADRASAH IBTIDAIYAH - Ubet, Abdulloh (Journal Of Islamic Elementary School (JIES), 2018)
Nowadays, sophisticated technology such as game is more interesting for children than reading or listening of literary work. Whereas there are some Islamic characters and cultural values that is found in a literary work, for instance short story. And it will influence toward the character of children. So, this research discusses about Islamic character and cultural values construction in short story of handle book at Islamic elementary school, setting as the background of the appearance of those values and also the construction form of those values. This research method is descriptive qualitative. It means that the data is words not numeric data. The result of this research is all short stories have Islamic character and cultural values. So there are twenty three positive values that can be taught toward the students.